ENTREPRENEURSHIP INTENTION: THE EFFECT OF FEAR AND ANXIETY OF COVID-19 AND OPPORTUNITY RECOGNITION - Aini, Edlyn Khurotul (Profit: Jurnal Adminsitrasi Bisnis, 2022)
The purpose of the study was to determine the effect of fear and anxiety of Covid-19 and opportunity recognition on self-efficacy and entrepreneurial intentions during the Coronavirus pandemic. The research sample consisted of 225 students of the Department of Business Administration, Universitas Brawijaya using purposive sampling. The hypothesis in this study was tested using PLS (Partial Least Square) analysis. The results showed that fear and anxiety in Covid-19 and opportunity recognition had a significant effect on self-efficacy, and opportunity recognition and self-efficacy had a significant effect on entrepreneurial intentions. Meanwhile, fear and anxiety of Covid-19 did not have a significant effect on entrepreneurial intentions. This research contributes practically by giving consideration to the University and policymakers to increase the intention and entrepreneurial activity of the student.